Microbiological study of vaginosis and predisposing factors in women in kalamoon region, Syria (Funded Work) - Sundus J. Yaseen,; Maisaa Abd-Alkareem,; Farah Yousef, (International Journal of Pharma and Bio Sciences, 2020)
Vaginal infection is one of the diseases of female lower genital tract, which is caused by various types of microorganisms such as bacteria, fungi and parasites. Our study aims to investigate the prevalence of vaginal infections in Kalamoon region, Syria. (vaginal swabs) were randomly collected from 46 women (18 pregnant and 28non-pregnant) aged 18 - 50 years. Specimens were obtained from the Medical City of Kalamoon University and al-Nabek Hospital between the period of February 2017 and July 2017. Five vaginal swabs were taken from each woman after using speculum. Microorganisms were detected by cultivation and biochemical tests.. Results showed that pregnant women had higher infection rate than non-pregnant ones. It is noted that the highest prevalence was of bacteria (76.75%) than fungi (23.25%) with the absence of Trichomonas vaginalis and Gardnerella vaginalis. This was proved by applying Gimsa test and direct microscopic test. Higher rates of infection were noticed in the age group of 36-50. The isolated microorganisms were gram-negative streptococci (11.62%), gram-positive streptostreptococci (97.67%), gram-negative bacilli (32.55%), gram-positive bacilli (39.53 %) and fungi (23.25%). The isolated streptococci were 32.55% Streptostreptococci and 65.11% Staphylococcus, amongst them there were (35.71%) for Staphylococcus aureus. No more investigation was done for gram negative streptococci. The prevalence of Candida Albicans was 2.32% and 20.93% for candida non- albicans. We had noticed an increase in fungal infections with pregnancy. We also studied the referred to the relationship between isolated microbes and methods of contraception; also we had determined microbes that were isolated in conjunction to the color of vaginal secretions. The relationship between each of bacterial infections and symptoms with presence of WBCs were also separately studied.